Da relação de herança entre construções inacusativas e construções aspectuais inceptivas e terminativas no português: uma análise construcional-cognitivista - Giovanna Cristina Rodrigues Alves Rafael (2023)
Based on the precepts of Cognitive Linguistics, auxiliary verb constructions which denote inceptive and terminative aspectual phases in Portuguese were investigated, based on the observation of the type productivity of verbs that occupy the position of V1 in the auxiliary verb constructions studied, but which present an unaccusative single-argument syntax when they are in lexical exercise, without there being, a priori, a robust change of meaning between the two constructions. In order to certify the unaccusativity of the four verbs selected for the analyses, tests proposed by Generative Theory were used, from which works on the phenomenon of unaccusativity depart; methodologically, however, this theory was restricted to such tests, for which there is no proposal within the theoretical framework adopted for the investigation. The postulates of Construction Grammar (GOLDBERG, 1995, 2006), Cognitive Grammar (LANGACKER, 2008), Conceptual Metaphor Theory (LAKOFF; JOHNSON, 2002[1980]), image schemas (TALMY, 2000) and the Theory of Mental Spaces (FAUCONNIER; TURNER, 1998) guided the analysis, in order to test the five suggested hypotheses and, consequently, to answer the research questions that fostered this work. Four auxiliary verb constructions were chosen as the object of study, whose V1 are, respectively, the verbs começar, principiar, acabar and terminar. Based on the analysis of a total of 192 constructions collected in the Corpus do Português, in the period between the 13th and 21st centuries, it was argued that there is an inheritance relationship between the unaccusative constructions and the auxiliary verb constructions that mark the inceptive and the terminative aspects. This relationship comes from a metaphorical cognitive operation at the base of which is the image schema of movement (motion). Concerning syntax, the inheritance relationship comes from the unaccusative construction with the postponed NP, whose processing does not exactly indicate a monoargumental construction, but a causative transitive construction with an elliptical subject. Thus, although there is a movement inheritance underlying both investigated constructional patterns, the unaccusative exercise of the four analyzed verbs did not prove to be totally synonymous with the one presented by the auxiliary verb constructions, especially when the single-argument construction is processed with the NP in front of the verb. It was proposed that the unaccusative constructions convey more the notion of operation on events, and that auxiliary verb constructions convey more the idea of operation on processes. Finally, regarding the process of linguistic change involved in the emergence of the auxiliary verb constructions researched, constructionalization proved to be more appropriate for the investigated case, since it was evidenced that the uses of each constructional pattern serve for different ideas, which even leads each of them to receive different nominations in the Portuguese constructicon: intransitive motion constructions and aspectual constructions of phases.